Effect of TRX Suspension Training on Balance, Mobility, Lower Limb Muscle Strength, and Fear of Falling in Older Men - Moradi, Masoud; Eskandari, Zohreh; Mirmoezzi, Masoud; Lashgari, Maryam (Faṣlnāmah-i ʻilmī-pizhūhishī-i, 2023)
Background and Aims Decreased muscle strength due to aging can lead to neuromuscular disorders, increased risk of falling, decreased function in daily activities, and reduced independence in the elderly. The present study aims to investigate the effect of eight weeks of TRX suspension training on lower limb muscle strength, balance, mobility, and fear of falling in older men. Methods This is a quasi-experimental. Participants were 30 elderly men with a mean age of 67.9±4.3 years who were assigned into two groups of TRX (n=16) and control (n=14). In the pre-test phase, lower limb strength was measured by the 30-second chair stand test, functional balance by the Berg balance scale, functional mobility by the timed up & go test, and fear of falling by the falls efficacy scale -international. Then, the TRX group performed the functional training for eight weeks, three sessions per week, each for about one hour. After performing the exercises, post-test assessments were performed in two groups. To compare the groups, the analysis of covariance and Bonferroni post hoc test were used in SPSS software, version 19. The significance level was set at 0.05. Results The TRX functional training significantly improved lower limb strength, balance, and functional mobility of the elderly (P≤0.001); however, it had no significant effect on their fear of falling (P>0.05). Conclusion Given the positive effects of TRX functional training on lower limb strength, functional balance, and mobility of elderly men, it seems that this suspension training can be used to improve lower limb muscle strength, functional balance, and mobility of older men.